Research of Bacterial Contamination of The Surgical Field During Phacoemulsification - T. Yu. Bogdanova; A. N. Kulikov; E. V. Danilenko; L. A. Kraeva (Oftalʹmologiâ)
Conditionally pathogenic conjunctival microflora is the most frequent cause of endophthalmitis after cataract phacoemulsification (“PEC”).The purpose. To evaluate the sterility of the surgical field and anterior chamber fluid (ACF) during elective (PEC).Materials and methods. 75 eyes were examined. Patients in the group I underwent standard treatment of the surgical field, in the group IA — the standard technique was supplemented with mechanical delimitation of the upper eyelid margin, in group II additional treatment of the surgical field with povidone iodine after blepharostat installation was performed. Microbiological material was collected preoperatively from three loci (conjunctival cavity, eyelid free margin, lacrimal ducts) and at different stages of surgery from the conjunctival cavity (after standard treatment, after blepharostat placement, after additional treatment). In addition, anterior chamber fluid (ACF) was examined — also during surgery. Microorganisms were identified by the MALDI-TOF method, sensitivity was determined by the discdiffusion method.Results. S. epidermidis prevails among all microorganisms. The percentage of the surgical field contamination by S.epidermidis after blepharostat setting was 33,33 %, 26 % and 40 % in the I, IA, II groups respectively; after additional treatment 6,6 % in the II group; in the ACF it was found in 23,33 %, 13 % and 0 % in the I, IA, II groups respectively.Conclusion. The additional treatment of the surgical field is the most effective technique to reduce the contamination of the conjunctival cavity by S.epidermidis after placing a blepharostat and the only one in the study to ensure its absence in the ACF. Standard treatments with and without mechanical delineation are less effective and do not prevent the contamination of the ACF.